Decomposition of ethnic heterogeneity on growth - Eiji Yamamura; Inyong Shin (Economics and Econometrics Research Institute (EERI), 2012)
Ethnic heterogeneity influences economic growth through various channels such as efficiency improvement and capital accumulation. However, it is open to discussion exactly how ethnic heterogeneity affects these channels. Hence, this paper attempts to examine the effects of heterogeneity on economic growth using data envelopment analysis. The empirical results of the estimations show that heterogeneity has a negative effect on efficiency improvements. However, heterogeneity has no effect on capital accumulation. This implies that ethnic heterogeneity hinders positive externalities such as information spillover, which hampers economic growth.
Keywords: H11; O43; 330; Ethnic fractionalization; Ethnic polarization; Efficiency improvement; Capital accumulation